A tale of two theories, a chronosequence and a bioindicator of soil quality. (June 2018) - Wardle, David A.; Ghani, Anwar
Abstract: In this Citation Classics commentary, we reflect upon a paper that we published in Soil Biology & Biochemistry in 1995 and that provided a critical assessment of the use of the microbial metabolic quotient ( qCO 2 or the ratio of microbial respiration to biomass) as a bioindicator of soil quality. This quotient is based on Eugene Odum's 'Theory of Ecosystem Succession' published in 1969 and has been widely used in soil ecology for over 30 years; a higher qCO 2 value is reflective of greater energetic inefficiency of the soil microbial biomass. At the time of our study a strong demand was emerging for easily measured soil quality bioindicators and qCO 2 was an obvious candidate. In our paper we drew on the plant ecological strategy theory of J. Philip Grime by highlighting that, in addition to the two major types of ecosystem identified in Odum's theory ('disturbed' and 'developed'), there is a third type, 'stressed' that is characterized by persistently harsh conditions (e.g., nutrient poor, cold, dry). We measured qCO 2 for soils collected from along the Franz Josef Glacier chronosequence in New Zealand that spans 120, 000 years and which includes all three types of ecosystems, going from disturbed to developed to stressed. We found that qCO 2 was least for the developed stage and was similarly high for the disturbed and stressed stages; it was not possible to discriminate between early successional stages characterized by high disturbance and high quality resource inputs from late successional stages characterized by substantial nutrient limitation and poor quality resource inputs. We further reanalyzed data from several publications from which qCO 2 could be calculated and these reinforced our empirical findings. Upon reflecting on our earlier work, we conclude that highly contrasting types of ecosystems that vary in their disturbance regime and stress cannot be arranged to any satisfaction along a unidimensional axis, and that no simple, unidimensional bioindicator (including qCO 2 ) is capable of adequately summarizing variation of soil quality among ecosystems. However, we also emphasize that despite its limitations as a bioindicator of soil quality, the qCO 2 concept has proven to be highly useful for advancing conceptual understanding of the functioning of the soil microbial community and its contribution to ecosystem processes.